Antiepileptic Drugs to Prevent Seizures After Spontaneous Intracerebral Hemorrhage: A Systematic Review and Meta-Analysis. Issue 5 (May 2019) - Angriman, Federico; Tirupakuzhi Vijayaraghavan, Bharath Kumar; Dragoi, Laura; Lopez Soto, Carmen; Chapman, Martin; Scales, Damon C.
Abstract : Background and Purpose—: We sought to evaluate the available literature to determine whether primary seizure prevention with antiepileptic drugs reduces the risk of poor outcomes and clinically relevant seizures among adult patients with spontaneous intracerebral hemorrhage. Methods—: Meta-analysis of observational studies and randomized controlled trials evaluating the use of any antiepileptic drug for primary seizure prevention among adult (≥18 years) patients with spontaneous intracerebral hemorrhage. The primary end point was poor clinical outcome at the longest recorded follow-up, defined as either a high (>3) modified Rankin Scale score or all-cause mortality during follow-up if the modified Rankin Scale score was not recorded. Early and late seizures were secondary outcomes. A random mixed effects model was used to estimate the pooled odds ratio of outcomes and associated 95% CI. Results—: We identified 7 studies with a total of 3241 patients for analysis of the primary outcome and 4 studies with a total of 1861 patients for analysis of the secondary outcomes. Overall, the use of antiepileptic drugs was not associated with a high Rankin Scale or all-cause mortality (odds ratio: 0.99; 95% CI, 0.66–1.49) or incident seizures (odds ratio: 0.89; 95% CI, 0.52–1.51) at the longest recorded follow-up time. Conclusions—: The use of antiepileptic drugs as primary prevention among adult patients with spontaneous intracerebral hemorrhage is not associated with improved neurological function during long-term follow-up. Future studies should focus on the preventive use of distinct antiepileptic agents among patients at high risk of both seizures and poor outcomes. Abstract : Supplemental Digital Content is available in the text.